1990
DOI: 10.1037/0022-3514.59.5.891
|View full text |Cite
|
Sign up to set email alerts
|

Attribution difficulty and memory for attribution-relevant information.

Abstract: This research compared the processing and retrieval of attribution-relevant information when the attributional inference is easy or difficult to make. Subjects attributed behavioral events to the person or to the situation, based on several items of context information. Each context sentence implied either the person or the entity as causal agent. When the attributional inference was difficult to make (an equal number of context sentences implied actor and entity as the causal agent), subjects recalled more of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(55 citation statements)
references
References 16 publications
(25 reference statements)
7
48
0
Order By: Relevance
“…While the strength of this study lies in the use of rich qualitative data focusing on specific points in the relationship, retrospective methodology raises alternative interpretations (Korsgaard et al., 2002), as attributions made at the time of the incident may affect memory for trustworthy behaviour. Although attributions can lead to reconstructed recall of events (e.g., Sedikides & Anderson, 1992), causal reasoning also enhances memory and accurate recall of attribution‐relevant information (i.e., behaviour and cues surrounding the event; Hamilton, Grubb, Acorn, Trolier, & Carpenter, 1990). Nonetheless, our results should be evaluated in view of possible recall biases inherent to such research designs.…”
Section: Discussionmentioning
confidence: 98%
“…While the strength of this study lies in the use of rich qualitative data focusing on specific points in the relationship, retrospective methodology raises alternative interpretations (Korsgaard et al., 2002), as attributions made at the time of the incident may affect memory for trustworthy behaviour. Although attributions can lead to reconstructed recall of events (e.g., Sedikides & Anderson, 1992), causal reasoning also enhances memory and accurate recall of attribution‐relevant information (i.e., behaviour and cues surrounding the event; Hamilton, Grubb, Acorn, Trolier, & Carpenter, 1990). Nonetheless, our results should be evaluated in view of possible recall biases inherent to such research designs.…”
Section: Discussionmentioning
confidence: 98%
“…Because our preliminary studies had indicated that subjects attributed outcomes to both internal and partner loci if given the opportunity, subjects in the main experiment were not given that option. Attributions were assessed by two items requiring a forced choice among Diagnostix, Image, or neither (e.g., Hamilton et al 1990) and two items on 7point scales anchored by Diagnostix and Image with a midpoint of "neither." Influence type can affect attitudes toward the influencer and about the behavior undertaken.…”
Section: Methodsmentioning
confidence: 99%
“…Given the mental role-playing in the experiment, one can question whether the subjects were sufficiently involved to internalize the manipulations and provide valid responses to the measures. The approach we adopted was modeled to a large extent after that used in psychology experiments studying attributions or influence, in which subjects are asked to offer their own perspectives about a hypothetical situation (e.g., Litman-Adizes, Fontaine, and Raven 1978;McGraw 1987;Russell and McAuley 1986;Schmidt and Weiner 1988;Weiner, Russell, and Lerman 1979) or to speculate about a hypothetical third party's reactions to a given scenario (e.g., Forgas, Bower, and Moylen 1990; Hamilton et al 1990; Shaw and Condelli 1986). Subjects in our experiment, however, were not simply given information about a situation in which successful influence was a fait accompli.…”
Section: The Body Of the Letter Then Presented The Appropriate Influementioning
confidence: 99%
“…Information that contrasts with earlier information is often better memorised than information that is congruent with preceding experience (27). Recall bias can also be suspected when the respondents report that they suspect that a certain factor is a risk factor (26).…”
Section: Selective Recallmentioning
confidence: 99%